Studies on the Compressive Behaviour of Aluminum–Zircon composites - Oluwaseyi Omotayo Taiwo; Abraham Kehinde Aworinde; Kenechukwu ThankGod Onyena; Darlington Chinaza Amadi; Binah Somtochukwu Ojiyi (Journal Majelis Paspama, 2026)
The use of Zircon (ZrSiO4) as reinforcement for aluminum (Al) alloys is generating interest due to its attractive properties. This has therefore made zircon a promising reinforcement for Al composites in automobile, aerospace, packaging and structural applications. While investigations on the mechanical responses of aluminum reinforced with zircon composites (especially hybrid composites) developed via stir casting has been extensively considered, limited works have been done on the compressive behaviour of single reinforced zircon composites. Hence, this work evaluates the compressive strength, compressive modulus, hardness, density, and impact strength of Al–ZrSiO4 composites produced by stir casting process. Compressive strength, hardness density increased with increasing zircon reinforcement while the compressive modulus and impact energy greatly reduced. Microstructural analysis confirms the presence and distribution of zircon particles.